Feasibility and effectiveness of adding object-related bilateral symmetrical training to mirror therapy in chronic stroke: A randomized controlled pilot study - Rodrigues L.C.* (2016)
© 2016 Taylor and Francis.Purpose: To evaluate the feasibility and effectiveness of adding object-related bilateral symmetrical training to mirror therapy (MT) to improve upper limb (UL) activity in chronic stroke patients. Method: Sixteen patients with moderate UL impairment were randomly allocated to either the experimental (EG) or control (CG) group. Both groups performed 1 hour sessions, 3 days/week for 4 weeks, involving object-related bilateral symmetrical training. EG performed the tasks observing their nonparetic UL reflected in the mirror, while CG observed the paretic UL directly. The primary outcome measure was unilateral and bilateral UL activity according to the Test dÉvaluation des Membres Supérieurs de Personnes Âgeés (TEMPA). All measurements were taken at baseline, post-training, and follow-up (2 weeks). Results: TEMPA total score showed the main effect of time. Significant improvement was found for bilateral but not unilateral tasks. Both groups showed gains after training, with no differences between them. Conclusions: This study showed the feasibility of adding object-related bilateral training to MT. Both types of training improved UL bilateral activity; however, a larger sample is required for a definitive study. Other studies need to be carried out to evaluate the effectiveness of combining more distal-oriented movements and object-related unilateral training to improve these effects in chronic stroke patients.